The recovery of intestinal barrier function and changes in oral microbiota after radiation therapy injury - Wang, Kun; Zhang, Jingjing; Zhang, Yihao; Xue, Junze; Wang, He; Tan, Xiaojie; Jiao, Xuelong; Jiang, Haitao (Frontiers in Cellular and Infection Microbiology, 2024)
Colorectal cancer (CRC), the third most prevalent malignant tumor, frequently necessitates neoadjuvant chemo-radiotherapy for advanced stages. Radiotherapy can impair the intestinal mucosal barrier, potentially leading to perioperative complications. The intestinal microbiota, a key component of this barrier, shows alterations in CRC patients, as evidenced by changes in oral microbiota. This study aims to evaluate immunoglobulin SIgA levels, inflammatory markers, and lymphocyte subset counts and ratios in intestinal mucosal samples at various intervals post-radiotherapy. The goal is to determine the optimal timing for surgery following radiotherapy and to identify potential probiotics or immunomodulators through high-throughput sequencing of bacterial 16s rRNA in saliva microbiota. This approach could offer novel strategies to mitigate perioperative complications stemming from radiotherapy-induced intestinal damage.